Is Future of Medicine Safe in the Hands of Young Medical Practitioners? Perceptions of Medical Students Regarding Academic Misconduct - Misbah, Samreen; Mashhadi, Syed Fawad; Zuberi, Fatima Ayaz; Ali, Elia; Fatima, Seerat; Haider, Khinshan; Saeed, Nasir; Riaz, Muhammad Umar (Pakistan Armed Forces Medical Journal, 2024)
Objective: To assess the self-reported attitude and behavior of MBBS students towards academic misconduct and to identify the differences of responses.Study design: Analytical cross-sectional study.Place and Duration of study: Army Medical College, Rawalpindi Pakistan, from May to Sep 2022.Methodology: MBBS students from first to final year of both genders who consented to participate were included in the study while excluding unwilling students. Data were collected from 396 medical students by convenience sampling using avalidated questionnaire by the University of Dundee. After formal ethical approval responses were obtained on 14 scenarios.Data were analyzed by using IBM SPSS Statistics version 26. For descriptive statistics frequency and percentages wereidentified, and Pearson’s Chi-Square test was used to find out the differences in responses among all year (p